2020
DOI: 10.3390/cells9071600
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ZC4H2 and RNF220 Inhibits Neural Stem Cell Proliferation and Promotes Neuronal Differentiation

Abstract: The ubiquitin E3 ligase RNF220 and its co-factor ZC4H2 are required for multiple neural developmental processes through different targets, including spinal cord patterning and the development of the cerebellum and the locus coeruleus. Here, we explored the effects of loss of ZC4H2 and RNF220 on the proliferation and differentiation of neural stem cells (NSCs) derived from mouse embryonic cortex. We showed that loss of either ZC4H2 or RNF220 inhibits the proliferation and promotes the differentiation ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…At present, it is well known that both RNF220 and its co-factor ZC4H2 are required for multiple neural developmental processes, including spinal cord patterning, cerebellum embryogenesis and function, and activity of the locus coeruleus ( 26 ). A study by Ma et al using Zc4h2 knockdown mice models revealed peculiar alterations in the V2a and V2b hindbrain and spinal cord interneurons, potentially implicating such features in the neuronal (and thus neurodevelopmental) phenotypes associated with WWS ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is well known that both RNF220 and its co-factor ZC4H2 are required for multiple neural developmental processes, including spinal cord patterning, cerebellum embryogenesis and function, and activity of the locus coeruleus ( 26 ). A study by Ma et al using Zc4h2 knockdown mice models revealed peculiar alterations in the V2a and V2b hindbrain and spinal cord interneurons, potentially implicating such features in the neuronal (and thus neurodevelopmental) phenotypes associated with WWS ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The different signal pathway regulation regulated the differentiation and proliferation of NSC. The differentiated signal pathway activity is relatively low or inhibited when proliferation is enhanced (53). In the present study, 1 µM BPA could promote human NSC proliferation and stemness.…”
Section: Discussionmentioning
confidence: 51%
“…Unexpectedly, in an RNA-seq analysis, few overlapping differentially expressed genes were identified in the ZC4H2 −/− and RNF220 −/− NSCs, suggesting the potential non-RNF220-dependent roles of ZC4H2 in NSCs; however, this requires further analysis (Zhang et al, 2020).…”
Section: P Otential Role S Of Rnf22 0/zc4h2 In Neur Al S Tem Cell Smentioning
confidence: 90%